RESEARCH OBJECT OF PRACTICE AT THE PEDAGOGICAL UNIVERSITY (ON THE EXAMPLE OF 4+2) - Sadulloeva Makhfuza Gaybulloevna (International Journal of Innovations in Engineering Research and Technology, 2022)
Effective organization of practice in pedagogical universities to improve the level of training of primary school students in the subjects of primary education in order to fulfill the requirements of the "Law on Education" based on the achievements of pedagogical technologies and information technologies Wide introduction in the period is one of the most important tasks of our time.